BIOMIND Portal for Developing 21st Century Skills and Overcoming Students' Misconception in Biology Subject - Vebrianto, Rian; Rery, Radjawaly Usman; Osman, Kamisah (International journal of distance education technologies, 2016)
This research was conducted to investigate the effectiveness of BIOMIND portal in enhancing students' 21st century skills and overcoming their misconceptions in Biology subject. 118 Indonesian high school students were involved in this quasi-experimental study. The experimental group underwent learning experiences using BIOMIND portal whereas the control group experienced conventional learning approaches. The effectiveness of the BIOMIND portal was measured based on the students' 21st century skills development and their level of misconceptions. There were significant differences in the 21st century skills development found between the experimental group and the control group. In addition, this research has found that the BIOMIND portal could overcome misconceptions among students due to the trainings given during interventions. This study concluded that teaching and learning using BIOMIND portal has brought positive impacts especially in developing the 21st century skills and overcoming students' misconceptions in Biology subject.